Analysis of Neoclassical Realism on Egypt's Decision to Stop Natural Gas Supply to Israel in 2012 - Riry, Yolansya Lisya Gibrilya; Suwecawangsa, Adi Putra; Parameswari, A.A.A Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
This research examines Egypt's decision to stop supplying natural gas to Israel in 2012 through an analysis of systemic and domestic factors. Egypt's reaction to Israel after the fall of dictator Mubarak seems contradictory to the commitments that have been fostered through the series of peace agreements back to 1978 and 1979. Despite the criticism and the risk of foreign aid cuts, Egypt continued to cancel Israeli gas contract. Neoclassical Realism approach is used by the researcher to analyze the factors that drove Egypt's decision to stop the natural gas supply to Israel using qualitative method. This research identifies that the pressures which occured in the Middle East and Eastern Mediterranean region, as well as its own domestic politics had led Egypt to this decision. Therefore, the interaction between both foreign and domestic politics has significantly influenced Egypt's foreign policy towards Israel. Keywords : Egypt, Israel, natural gas supply, Neoclassical Realism